The Impact of Universal Health Coverage Policies on Health Equity Metrics: A Longitudinal Analysis in Indonesia - Firman Hadi; Annisa Annisa; Utter Prakesh; Aleisha Wulandari (HM Publisher, 2025)
Indonesia has made significant strides towards Universal Health Coverage (UHC) with the implementation of the Jaminan Kesehatan Nasional (JKN) program. However, achieving equitable health outcomes across diverse socioeconomic and geographic groups remains a challenge. This study investigates the longitudinal impact of UHC policies on key health equity metrics in Indonesia. This study employed a longitudinal, quasi-experimental design using a difference-in-differences (DID) approach. Data were collected from a nationally representative sample of Indonesian households from 2014 (pre-JKN expansion) to 2022. The dataset included socioeconomic indicators (wealth quintiles, education, geographic location), health service utilization (antenatal care visits, skilled birth attendance, immunization rates), and health outcomes (under-five mortality rate, stunting prevalence). The DID analysis compared changes in these metrics between groups with varying levels of pre-existing health insurance coverage and socioeconomic status. Multivariable regression models were used to control for confounding factors. The DID analysis showed that UHC expansion was associated with significant improvements in health service utilization, particularly among lower socioeconomic groups. Antenatal care visits increased by an estimated 15% (95% CI: 12-18%) in the lowest wealth quintile compared to a 5% (95% CI: 3-7%) increase in the highest quintile. Skilled birth attendance similarly increased disproportionately among disadvantaged groups. However, while under-five mortality and stunting prevalence decreased overall, significant disparities persisted. The reduction in under-five mortality was smaller in the lowest wealth quintile (10% reduction, 95% CI: 7-13%) compared to the highest (18% reduction, 95% CI: 15-21%). Regression models confirmed that socioeconomic status remained a significant predictor of health outcomes even after controlling for UHC coverage. In conclusion, while Indonesia's UHC policies have improved access to healthcare services, particularly for vulnerable populations, significant health equity gaps remain. Addressing these disparities requires a multi-pronged approach that goes beyond financial protection and includes targeted interventions to address social determinants of health, improve health service quality, and enhance health literacy among disadvantaged communities.